Therapeutic potential of hAECs for early Achilles tendon defect repair through regeneration. (17th November 2017) - Barboni, Barbara; Russo, Valentina; Gatta, Valentina; Bernabò, Nicola; Berardinelli, Paolo; Mauro, Annunziata; Martelli, Alessandra; Valbonetti, Luca; Muttini, Aurelio; Di Giacinto, Oriana; Turriani, Maura; Silini, Antonietta; et al.
Abstract: Cell‐based therapy holds great promise for tendon disorders, a widespread debilitating musculoskeletal condition. Even if the cell line remains to be defined, preliminary evidences have proven that amniotic‐derived cells possess in vitro and in vivo a great tenogenic potential. This study investigated the efficacy of transplanted human amniotic epithelial cells (hAECs) by testing their early regenerative properties and mechanisms involved on a validated ovine Achilles tendon partial defect performed on 29 animals. The injured tendons treated with hAECs recovered rapidly, in 28 days, structural and biomechanical properties undertaking a programmed tissue regeneration, differently from the spontaneous healing tissues. hAECs remained viable within the host tendons establishing with the endogenous progenitor cells an active dialogue. Through the secretion of modulatory factors, hAECs inhibited the inflammatory cells infiltration, activated the M2 macrophage subpopulation early recruitment, and accelerated blood vessel as well as extracellular matrix remodelling. In parallel, some in situ differentiated hAECs displayed a tenocytelike phenotype. Both paracrine and direct hAECs stimulatory effects were confirmed analysing their genome profile before and after transplantation. The 49 human up‐regulated transcripts recorded in transplanted hAECs belonged to tendon lineage differentiation (epithelial–mesenchymal transition, connective specific matrix components, and skeleton or muscle system development‐related transcripts), as well as the in situ activation of paracrine signalling involved in inflammatory and immunomodulatory response. Altogether, these evidences support the hypothesis that hAECs are a practicable and efficient strategy for the acute treatment of tendinopathy, reinforcing the idea of a concrete use of amniotic epithelial cells towards the clinical practice.